From lives at the margins to syncretism and cultural blending: A critical perspective to the notions of identity and culture from a global approach (2019)
Globalization process has raised important questions, among others, derived from its effects on identities and cultures. Although there are those who contemplate it with skepticism because they consider it implies new forms of domination or leads to the disappearance of differences that have forged group, national or religious identities, others considers it an opportunity for the creation of spaces characterized by common meanings and languages. The purpose of this article is to present, from the perspective of the study of history and through the lens of Global approaches, some elements around the notions of identity and culture that try to overcome essentialist interpretations and considers their frequent and constant configuration as a result of contacts, borrowings and mixing processes which are not necessarily assumed as a product of the imposition and violence, but also as a result of adaptations, accommodations and improvisations in the relationship between different human groups. © 2019 Universidad del Norte. All rights reserved.